Will You Die for Your Country? Workplace Death in an Era of Mass Incarceration. Issue 4 (28th August 2020) - Strader, Eiko; Hines, Miranda
Abstract : People with criminal records in the United States continue to face limited employment opportunities due to social stigma and legal barriers. In contrast to the civilian sector, the military conducts a "whole person" evaluation to screen potential recruits and regularly hires people with felony and misdemeanor records. Moreover, evidence suggests that the military serves as a socially integrative institution and may facilitate desistance from future crimes. However, critics argue that the military exacerbates inequalities by subjecting marginalized communities to the unequal burden of service. Using the data obtained from the Army, we examine the relative risks of combat exposure and casualties between enlisted soldiers with and without criminal records who joined between 2002 and 2009. The results suggest that soldiers with felony and misdemeanor records are more likely to be assigned to combat occupations than those without criminal records. We also find that among soldiers assigned to positions with low combat exposure, ex‐offenders face a higher risk of death compared to those without criminal records. Findings do not dispute the idea that the military facilitates desistance from future crimes and provides second chances to people with criminal records, but reaffirm the fact that military service costs lives and limbs.